Registration and regulation of foreign investments and enterprises - Abdulai, Taiwo (Lagos : Goodwill House, 1999)
This publication attempts to summarise the investment laws and practice as at 1st March, 1999.
osc 25/07/2016
Loans
Keywords: Investments - Laws and regulations; Nigeria